Pengenalan Teknologi Informasi Pada Siswa MTsN 4 Tanah Laut - Zulfahri, Aidil Fajar; Herpendi; Aristi, Nina Mia; Rizki, Afian Syafaadi; Hafizd, Khairul Anwar; Fathurrahmani (Jurnal Masyarakat Indonesia (Jumas), 2025)
The development of digital technology today has transformed the way its users carry out activities, making the involvement of Information Technology highly essential in supporting daily life. Currently, the use of Information Technology has become commonplace and highly beneficial in various fields of human life. Unfortunately, many school students today only use electronic devices for entertainment, without utilizing them for learning and enhancing their knowledge. MTsN 4 Tanah Laut, as one of the educational institutions under the Ministry of Religious Affairs, has faced significant changes due to the Covid-19 pandemic. Although the pandemic has now ended, knowledge and skills in using Information Technology remain important, especially with the adoption of computers or laptops in the school learning process. Therefore, Information Technology introduction training is crucial for MTsN 4 Tanah Laut students to improve their understanding and skills in utilizing Information Technology. The purpose of this community service is to help students develop technological skills, enhance students’ understanding of digital literacy, improve learning efficiency, encourage creativity and innovation, prepare students for the workforce, promote positive use of technology, and foster research and innovation in the field of education. This community service is conducted through lectures and discussions on the introduction of information technology. The results of the research show an increase in participants' understanding of information technology.